Taking liberties: the war on terror and the erosion of American democracy - Herman, Susan N. (Oxford Univ. Press, 2011)
Machine generated contents note: -- Introduction -- PART I: DRAGNETS AND WATCHLISTS -- Chapter 1 The Webmaster and the Football Player -- The Material Support Dragnet -- The Football Player -- The Material Support and Material Witness Dragnets -- Chapter 2. "Foreign Terrorist Organizations," Humanitarians, -- and the First Amendment -- The Iranian Democrat -- Peacemakers and Humanitarians -- Chapter 3. Charity at Home -- The Campaign against Charities -- Collateral Damage to Freedom of Religion and Association -- Chapter 4 Traveling with Terror -- Watching the Watchlists -- Security Theater? -- The Rights of Others -- Chapter 5 Banks and Databanks -- Financial Institutions as TIPSters -- Watchlists and the Private Sector -- Does It Work? -- Collecting the Dots -- Why Should I Care? - Privacy and Democracy -- PART II - SURVEILLANCE AND SECRECY -- Chapter 6 Gutting the Fourth Amendment -- The Fourth Amendment and Terrorism -- "Foreign" Intelligence Surveillance, Americans, and the Patriot Act -- Mayfield v. United States Part II -- The Secret Court and the One-Sided Litigation -- A Job for Congress and the Courts -- Chapter 7 The Patriot Act and Library/Business Records -- American Librarians -- Judicial Fumbling -- Third Party Records and the Fourth Amendment -- Reconsidering the "Library Provision" -- Chapter 8 Gagging the Librarians -- The Library Connection -- Other Librarian Tales -- Chapter 9 John Doe and the National Security Letter -- Why National Security Letters? -- John Doe and Victor Marrero -- Loosening the Gag -- Fourth Amendment Rights for NSL Recipients -- First Amendment Rights for Internet Users -- The Inspector General Expos©♭s 2007-2010 -- National Security Letters, the Fourth Amendment, and Congress -- Chapter 10 The President's Surveillance Program -- In the Halls of the Department of Justice -- The Rubber Stamp Congress -- Closing the Courthouse Doors -- Post-FAA Litigation -- The Secret Court Strikes Again -- "What Else Is It That We Don't Know?" -- PART III: RESTORING CHECKS AND BALANCES -- Chapter 11 American Democracy - The President, the Congress, and the Courts -- The View from the Oval Office - From Bush to Obama and Beyond -- The Sleeping Watchdog -- Secrecy and the Courts -- The Eclipse of the Courts -- Conclusion -- Ordinary Americans -- Restoring Balance